2008
DOI: 10.1007/s00128-008-9548-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity on Biodegradation of Polycyclic Aromatic Hydrocarbons (PAHs) of Heavy Crude Oil in Soil

Abstract: The spillage of crude oil in the soil damages the environment. Polycyclic aromatic hydrocarbons (PAHs) are one of the crude oil components that may be harmful for living organisms. PAHs can disappear from the environment by volatilization and biodegradation. The effect of different NaCl concentrations (0%-5%) on PAHs reduction from the heavy crude oil-contaminated soil was studied. Our results showed that increasing NaCl concentration in soil had decreasing effect on total crude oil and PAHs reduction. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…To support the growth of bacterial cells, nutrients such as glucose, yeast extract and acetate were added. Tehrani et al (2009) reported the effect of salinity on biodegradation of PAHs of heavy crude oil. Head et al (2006) described the importance of additional nutrients in the bioremediation of petroleum hydrocarbons.…”
Section: Description Of Va3 Strain (Stenotrophomonas Maltophilia)mentioning
confidence: 99%
“…To support the growth of bacterial cells, nutrients such as glucose, yeast extract and acetate were added. Tehrani et al (2009) reported the effect of salinity on biodegradation of PAHs of heavy crude oil. Head et al (2006) described the importance of additional nutrients in the bioremediation of petroleum hydrocarbons.…”
Section: Description Of Va3 Strain (Stenotrophomonas Maltophilia)mentioning
confidence: 99%
“…At present, microbial remediation of oil contaminated soil has been carried out and widely reported in the world (7,16,23,26), which provides a reference and guidance for development and practical application of bioremediation technology. in this research, 10 natural bacterial strains were isolated from oil contaminated soil from the Daqing oilfield in northern China, and identified by 16S rDNA sequence analysis combined with morphological observation, physiological and biochemical tests.…”
Section: Introductionmentioning
confidence: 99%
“…aeruginosa isolate 312A had the highest rate of degradation 71% after 48 days at pH 7.0 at 30ºC. (Dariush et al, 2009) reported that total PAHs (phenanthrene, anthracene and pyrene) degradation was observed in 1% NaCl (35%).…”
Section: Discussionmentioning
confidence: 98%